DIRECTIONS FOR IMPROVEMENT OF STATE FISCAL (BUDGETARY-TAX) POLICY - Asatullaev Khurshid Sunatullaevich (Ecominds Press, 2025)
At the present stage of innovative development of the economy, it is necessary to develop new directions of regulation by the state in order to achieve sustainable development of the economy and solve emerging problems. Effective implementation of state fiscal (budget and tax) policy aimed at achieving economic development and increasing economic activity is an urgent problem that requires study. Because the global pandemic observed in recent years and the imbalances and serious complications caused by it require us to draw conclusions. State fiscal (budget and tax) policy is aimed at increasing economic activity and eliminating unfavorable situations in the economy through the rational use of financial resources. The article presents proposals and conclusions aimed at increasing economic growth, investment and innovation activity, employment of the population through the rational use of economic levers of the state fiscal (budget and tax) policy.
Keywords: State fiscal policy, budget and tax policy, employment, finance, state budget, state budget expenditures, state budget revenues, economic crisis, economic cycle, taxes, tax breaks.